Effects of dried distillers grains with solubles on pork loin quality and sow fat quality - Gipe, Amanda Nicole (Kansas State University, 2008)
Two experiments were conducted to determine the effects of dried distillers grains with solubles (DDGS) on pork loin and fat quality. In the first experiment, 1,160 barrows (PIC) were used in a 70-d study to determine the influence of DDGS and glycerol on pork loin and fat quality attributes. Barrows were fed a corn-soybean meal based diet with the addition of selected levels of DDGS (0 or 20%) and glycerol (0, 2.5, or 5%) feed stuffs. Loins from the two heaviest pigs in each pen were removed for evaluation of pork loin and fat quality. Experiment two was a pilot study, in which eight non-pregnant sows were fed either 0 or 50% DDGS with a corn soybean meal based diet for 92-d. In the first experiment, there were no DDGS x glycerol interactions for purge loss %, instrumental color (L*a*b*), visual color, marbling score, drip loss %, visual color, pH, Warner-Bratzler shear force (WBSF), cook loss %, myofibrillar tenderness, juiciness, pork flavor intensity, connective tissue amount, and overall tenderness. There was a DDGS x glycerol interaction (P<0.03) for off-flavor intensity. Pigs fed diets with 20% DDGS had higher WBSF values, lower myofibrillar tenderness, lower overall tenderness scores, lower connective tissue scores, and had more off-flavors (P<0.05). Loin fatty acid analysis revealed an increase in palmitoleic, linoleic, and eicosadienoic acids (P<0.05) and iodine value (P<0.03) for pigs fed 20% DDGS. In the second experiment, there were no differences (P>0.64) in BW or backfat change for sows fed either 0 or 50% DDGS. No differences (P>0.23) in lipid oxidation from lean trimmings as measured by 2-thiobarbituric acid reactive substances (TBARS) assay were reported either initially or after 5 d of retail display for sows fed either 0 or 50% DDGS. As expected, lipid oxidation increased (P<0.003) as measured by TBARS assay for both treatments from d 1 to 5. Jowl fatty acid analysis revealed an increase in linoleic acid (P<0.01), total polyunsaturated fatty acids (P<0.01), and the ratio of polyunsaturated fatty acids to saturated fatty acids (P<0.03) for sows fed 50% DDGS.
Keywords: carcass fat quality; DDGS; glycerol; pork quality; sow; tenderness; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Food Science and Technology (0359)